Portraying Cendekia Leadership in the Perspective of Ki Hajar Dewantara’s Trilogy - Antoni Ludfi Arifin; Eric Hermawan (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to describe the Cendekia leadership from the personality perspective of Ki Hajar Dewantara, the father of education in Indonesia. This research is a qualitative study that uses literature study as the method. Seven articles published in the national journal were used as the data of this study and then analyzed using content analysis method.  The results of the discussion of cendekia leadership in the perspective of Ki Hajar Dewantara's character from the first philosophy are (1) Ing Ngarso Sung Tuladha; good leadership must behave and speak well and become a role model, discipline, able to be role model for everyone, innovators, protector, educator, honest, wise, and serve wholeheartedly, (2) Ing Madya Mangun Karsa means always help other, motivating and encouraging to work hard, inspiring, have a sense of empathy and sympathy, as well as able to collaborate, (3) Tut Wuri Handayani means that a leader who can encourage his subordinates to be at the forefront of achievement and individuals who are strong in facing obstacles, smart, creative, have a sense of justice, giving freedom to express themselves, and encourage people to be independent, effective, and efficient at work.